2018
DOI: 10.18805/ijare.a-4922
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimum crop mix for crop cultivation in Kerala homesteads

Abstract: Homestead farming has been the backbone agricultural economy of Kerala but the productivity of the homesteads in Kerala has yet to reach an acceptable level. In this paper the possibility of increasing the contribution of this sector through proper crop planning is sought. The optimum model was developed by using linear programming (LP) technique. The constraints included in the analysis were total area, intercropped area, investment amount and population of each enterprise. The optimum model reveal the sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Most of the literatures reviewed here are articles that used linear programming decision support systems for crop mix and cropping pattern (65%) while the remaining are articles that employed linear programming to promote the performance of dairy farms, crop-livestock integration, land and water resource use, arable crops and fisheries enterprises, botanical farm, and other forms of land use with the aim of maximizing net income, maximizing gross income, improving food security, and enhancing livelihood performance. Outlined results suggested that using LP as decision making tool in agriculture provides maximum annual return (Sarker et al, 1997;Hassan et al, 2005;Fallah Shamsi, 2010;Mohamad and Said, 2011;Alabdulkader et al, 2012;Felix et al, 2013;Geta et al, 2013;Andreea and Adrian, 2013;Gadge et al, 2014;Mugabe et al, 2014;Buzuzi and Buzuzi, 2018;Muhammed Jaslam et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the literatures reviewed here are articles that used linear programming decision support systems for crop mix and cropping pattern (65%) while the remaining are articles that employed linear programming to promote the performance of dairy farms, crop-livestock integration, land and water resource use, arable crops and fisheries enterprises, botanical farm, and other forms of land use with the aim of maximizing net income, maximizing gross income, improving food security, and enhancing livelihood performance. Outlined results suggested that using LP as decision making tool in agriculture provides maximum annual return (Sarker et al, 1997;Hassan et al, 2005;Fallah Shamsi, 2010;Mohamad and Said, 2011;Alabdulkader et al, 2012;Felix et al, 2013;Geta et al, 2013;Andreea and Adrian, 2013;Gadge et al, 2014;Mugabe et al, 2014;Buzuzi and Buzuzi, 2018;Muhammed Jaslam et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…2. Used to optimize profit, to examine whether or not profit increased after implementing the model [5], [10]. 3.…”
Section: A Uses Of Lp Modelmentioning
confidence: 99%